2018
DOI: 10.1002/gj.3410
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and tectonic setting of the Bulage PbZn deposit, Inner Mongolia, China: Evidence from geology, fluid inclusions, EMPA, H–O isotope systematics, zircon U–Pb geochronology, and geochemistry

Abstract: The recently discovered Bulage Pb-Zn deposit is located in the central part of the Erlianhot-Dongwuqi Metallogenic Belt (eastern Central Asian Orogenic Belt) in Inner Mongolia, China. The ore bodies of the deposit are hosted in alkali feldspar granite and in dacitic crystal tuff within Unit 2 of the Carboniferous Baoligaomiao Formation.The Bulage deposit is a low to moderate temperature hydrothermal vein-type deposit and is controlled by fractures. The hydrothermal mineralization can be divided into three stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In summary, the whole-rock geochemical composition reported in this study shows that the Paleoproterozoic adakitic rocks in the Qingchengzi district are characterized by high Al 2 O 3 and SiO 2 contents and Sr/Y ratios, LREEs and LILEs enrichment, and HREEs and HFSEs depletion ( Supplementary Table S2). Combining the Hf isotopic characteristics, these granitoids are derived from the partial melting of the Meso-Neoarchean thickened lower crust material, consistent with the magmatic rocks formed in the tectonic setting of an active continental margin or island arc (e.g., [83][84][85][86]). In addition, previous studies have shown that the JLJB Paleoproterozoic volcanic rocks (e.g., Liaohe Group) are calc-alkaline series and show the characteristics of I-type granites, and they were formed in an volcanic arc environment [34].…”
Section: Implications For Tectonic Settingmentioning
confidence: 72%
“…In summary, the whole-rock geochemical composition reported in this study shows that the Paleoproterozoic adakitic rocks in the Qingchengzi district are characterized by high Al 2 O 3 and SiO 2 contents and Sr/Y ratios, LREEs and LILEs enrichment, and HREEs and HFSEs depletion ( Supplementary Table S2). Combining the Hf isotopic characteristics, these granitoids are derived from the partial melting of the Meso-Neoarchean thickened lower crust material, consistent with the magmatic rocks formed in the tectonic setting of an active continental margin or island arc (e.g., [83][84][85][86]). In addition, previous studies have shown that the JLJB Paleoproterozoic volcanic rocks (e.g., Liaohe Group) are calc-alkaline series and show the characteristics of I-type granites, and they were formed in an volcanic arc environment [34].…”
Section: Implications For Tectonic Settingmentioning
confidence: 72%
“…As mentioned in the previous section, the continent–continent collision between the YZC and NCC during the Triassic represents the initial cratonic destruction in the eastern NCC. However, the subduction and closure of the Carboniferous–Permian Paleo‐Asian Ocean introduced the initial cratonic destruction of the northern margin of the NCC (e.g., Xiao et al, ; Windley, Alexeiev, Xiao, Kröner, & Badarch, ; Safonova et al, ; Pei et al, , Pei et al, ; J. Li et al, ). This denotes that the cratonic destruction of the NCC is heterogeneous (Y. G. Xu, Li, et al, ), and this heterogeneity is related to different dynamic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The NCC is an Archean to Paleoproterozoic cratonic block, which has been overprinted by the deformational, thermal, and magmatic effects of several Proterozoic orogenies, unlike true Precambrian cratons; in addition, it has been subjected to Phanerozoic accretion, collision, and subduction along its northern, southern, and eastern margins, respectively (Hart et al, ). To the north, the closure of the Paleo‐Asian Ocean occurred during the Late Permian to the Middle Triassic (Xiao, Windley, Hao, & Zhai, ; Li, ; Wu, Li, Yang, & Zheng, ; Wu et al, ; Cao et al, ; J. Li et al, ). In the south, the NCC was affected by the subduction and collision of the continental crust of the Yangtze Craton (YZC) during the Triassic (Dong et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%